Os desafios e possibilidades da abordagem Orff-Schulwerk na formação dos professores - Abdalla, Gabriela Vasconcelos (2025)
The general aim of this study is to analyze the social representations of teachers who are members of the Associação Orff Brasil (Abraorff) regarding the challenges and possibilities related to the Orff-Schulwerk approach. Its specific objectives are: 1) to contextualize the Orff-Schulwerk approach in the context of the history of music education, in order to understand its foundations and principles; 2) to identify the possibilities and challenges that are perceived by the participants as relevant to their practices; and 3) to propose a teacher training project in the Orff-Schulwerk approach based on the social representations (SR) analyzed. The study is grounded in the Theory of Social Representations (Moscovici, 2012), the Orff-Schulwerk approach (Orff, 1978), and other authors related to teacher training and music education. It follows a qualitative research approach, developed through a brief profile questionnaire and the use of the Free Word Association Technique (TALP), along with drawings created by the participating teachers, aimed at understanding the meaning of Orff-Schulwerk, its challenges and possibilities. The data obtained were analyzed through the content analysis technique (Bardin, 2007) and theoretical-methodological references, resulting in two analytical dimensions: 1st Possibilities of the OS approach and its categories: a) social space and human relationships and coexistence; b) music, movement and language; and c) experimenting, improvising and creating; 2nd Challenges related to the OS approach and its categories: a) working conditions and professional devaluation; b) overcoming difficulties and didactic strategies; c) the challenges related to the foundations of the OS. The results highlight possibilities: accessibility and collectivity, valued in the social dimension; as well as flexibility and creativity, present in the principles of OS, and which incorporate practice and reflection in a participatory and dynamic process. As challenges are identified: working conditions; professional devaluation; difficulties in sharing and justifying actions as a teacher to the school and/or non-school community; theorization of foundations and practices related to Music Education; as well as adaptability and co-construction of the OS. Despite the challenges to be faced, teacher’s SR reveal their potential through artistic, creative, emotional, social and cognitive skills, defended by the pedagogical principles of OS. Finally, a permanent training project is proposed, focused on an intercultural perspective aimed at diversity and social inclusion. It is hoped, therefore, that music education can contribute with pedagogical practices that address the social, cultural and educational challenges present in contemporary Brazilian society